2009
DOI: 10.1002/ppul.20965
|View full text |Cite
|
Sign up to set email alerts
|

Levels of pollutants in indoor air and respiratory health in preschool children: A systematic review

Abstract: The aim of this paper is thus to identify, evaluate, and summarize in a systematic fashion all the epidemiological studies that have analyzed the association between exposure to specific indoor air pollutants and respiratory disease among children under the age of five. A search was carried out in the main biomedical bibliographic sources in December 2006 and updated in February 2008. The study period covered 12 years (1996-2007). All the selected papers were carefully read. We focused on studies that analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…Our previous study in Nanjing provided the associations between dry cough and sensation of stuffy odor, unpleasant odor, pungent odor, moldy odor, humid air, and dry air (P < 0.05) 37 . Environmental tobacco smoke exposure has been reported to be associated with cough 38 , but some studies found no relation between dry night cough and smoke exposure 39,40 . However, a pooled analysis of 53 879 children from 12 cross-sectional studies found strong evidence linking nocturnal cough to smoking during pregnancy, smoking during the first two years and parental current smoking 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study in Nanjing provided the associations between dry cough and sensation of stuffy odor, unpleasant odor, pungent odor, moldy odor, humid air, and dry air (P < 0.05) 37 . Environmental tobacco smoke exposure has been reported to be associated with cough 38 , but some studies found no relation between dry night cough and smoke exposure 39,40 . However, a pooled analysis of 53 879 children from 12 cross-sectional studies found strong evidence linking nocturnal cough to smoking during pregnancy, smoking during the first two years and parental current smoking 1 .…”
Section: Discussionmentioning
confidence: 99%
“…We note that the existing quality assessment tools do not incorporate assessment of the quality of the exposure information; consequently, studies rated as strong methodologically could have weak methods of quantifying personal VOC exposures. We believe this systematic review to have been more rigorous than the previous, frequently cited, systematic review [76], critical analysis [77] and literature review [78], which notably did not critically appraise study quality using validated tools or distinguish between studies investigating aetiology and those investigating established disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of wheezing was 7.4% among 10 to 12 year-old children in central Taiwan [Liao et al, 2009], 25.6% among 7 to 15 year-old children in a industrial area of India [Kumar et al, 2007], 8.4% among 11 to 15 year- old Chinese children [Zhao et al, 2008] and 12.6% among 13–15 year-old children in Poland [Kasznia-Kocot et al, 2010]. Most epidemiological studies have assessed the association of indoor unclean cooking fuel exposure and respiratory health or outdoor traffic-related air pollution and respiratory health separately [Rehfuess et al, 2009; Weinmayr et al, 2010; Andersson et al, 2011] Further, studies on exposure to biomass fuel use and respiratory health studies have mostly been conducted among preschool children [Dherani et al, 2008; Fuentes-Leonarte et al, 2009]. Studies comparing respiratory health of school age children living in households using unclean cooking fuel in different outdoor air pollution settings are limited.…”
Section: Introductionmentioning
confidence: 99%